2020
DOI: 10.1038/s41375-020-0828-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic measles virus therapy enhances tumor antigen-specific T-cell responses in patients with multiple myeloma

Abstract: Oncolytic virus therapy leads to immunogenic death of virus-infected tumor cells and this has been shown in preclinical models to enhance the cytotoxic T-lymphocyte response against tumor-associated antigens (TAAs), leading to killing of uninfected tumor cells. To investigate whether oncolytic virotherapy can increase immune responses to tumor antigens in human subjects, we studied T-cell responses against a panel of known myeloma TAAs using PBMC samples obtained from ten myeloma patients before and after syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 41 publications
(57 reference statements)
1
58
0
2
Order By: Relevance
“…Remarkably, one MM subject who obtained CR after MV-NIS treatment had intense T-cell reactions to MS proteins and to most of the examined TAAs. These findings confirmed that OVs can operate as an antigen vaccine, rising the activity of T-lymphocyte against TAAs in MM subjects [ 91 ].…”
Section: Antitumoral Action Of Oncolytic Virusessupporting
confidence: 72%
See 1 more Smart Citation
“…Remarkably, one MM subject who obtained CR after MV-NIS treatment had intense T-cell reactions to MS proteins and to most of the examined TAAs. These findings confirmed that OVs can operate as an antigen vaccine, rising the activity of T-lymphocyte against TAAs in MM subjects [ 91 ].…”
Section: Antitumoral Action Of Oncolytic Virusessupporting
confidence: 72%
“…This result was validated by several experimentations. Packiriswamy et al evaluated T-cell activities against a group of MM TAAs employing PBMC derived from MM subjects before and after utilization of a MV-NIS [ 91 ]. MV-NIS treatment remarkably increased T-cell activities against MAGE-C1 and MAGE-A3.…”
Section: Antitumoral Action Of Oncolytic Virusesmentioning
confidence: 99%
“…In four ovarian cancer patients treated with MV-NIS, IFN-γ and IL-4 responses against the tumor antigens FRα and IGF binding protein 2 (IGFBP2) were detected by ELISPOT [ 122 ]. Increases in IFN-γ ELISPOT counts against cancer testis antigens were also observed in the majority of tested multiple myeloma patients treated with MV-NIS [ 123 ]. The myeloma patient with an exceptional response to MV-NIS had a high mutational load and high baseline T cell responses against several tumor antigens, which remained stable after virotherapy.…”
Section: Immunovirotherapymentioning
confidence: 99%
“…Oncolytic infection and type I IFN concomitantly induce the upregulation of checkpoint receptor ligands such as PDL1, and thus combination therapy with pharmacologic or viral expression of checkpoint blocking antibodies with vaccinia [ 67 ], VSV [ 68 , 76 ], reovirus [ 77 ], measles [ 70 , 78 ], HSV [ 72 ] and NDV [ 71 ] have provided superior tumour outcomes. Immune correlative studies in the clinical setting have corroborated preclinical findings, showing that talimogene laherparepvec (HSV) and reovirus treatment promotes an increase in CD8 T cell density in post treatment biopsies [ 79 , 80 ], and measles treatment facilitates T cell priming against tumour antigens [ 81 ]. The representation of virus specific or tumour antigen specific T cells which infiltrate into a tumour is not well characterized, however is likely to be skewed toward viral specificities due to high level expression of viral epitopes which are not subject to tolerance mechanisms.…”
Section: Tme Make Over By Oncolytic Virusesmentioning
confidence: 99%